1979
DOI: 10.1007/bf00333098
|View full text |Cite
|
Sign up to set email alerts
|

Cloning the trpR gene

Abstract: In Escherichia coli, the structural gene for purine nucleoside phosphorylase, deoD, is subject to insertional inactivation by prophage lambda. From one such secondary site lambda lysogen, strain SP265, one may isolate deletions that remove all or part of the trpR gene and other genes in the deo-thr sector of the E. coli chromosome. Specialized transducing phages harboring serB+ and trpR+ were liberated following induction of SP265. All such phages were N-defective, bio-type pseudolysogens whose DNA persisted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0

Year Published

1980
1980
2005
2005

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 33 publications
1
35
0
Order By: Relevance
“…The dye gene, whose loss leads to sensitivity to dyes such as toluidine blue, maps near the thr operon (41). We found that the strain ECL547 (arcA ) is dye-resistant, and the mutant ECL549 (arcAl) is dye-sensitive on tryptone/toluidine-blue agar (14).…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…The dye gene, whose loss leads to sensitivity to dyes such as toluidine blue, maps near the thr operon (41). We found that the strain ECL547 (arcA ) is dye-resistant, and the mutant ECL549 (arcAl) is dye-sensitive on tryptone/toluidine-blue agar (14).…”
Section: Resultsmentioning
confidence: 87%
“…Mutations in the dye gene also confer resistance to malespecific phages ( (14). On the basis of altered protein profiles of inner and outer membranes in such mutants, the gene is thought to affect the synthesis of envelope proteins (43,44).…”
Section: Resultsmentioning
confidence: 99%
“…The Escherichia coli gene arcA was identified initially in deletion strains as a locus near trpR conferring sensitivity to redox dyes such as methylene or toluidine blue (Dye phenotype) and resistance of Hfr strains to donor-specific RNA bacteriophages (Msp phenotype) (8,27). Lerner and Zinder (20), Beutin and Achtman (4), and Silverman et al (29) all isolated mutants defective in F-plasmid-dependent DNA donor activity in which the responsible mutation mapped to the trpR-thr region; each laboratory assigned a different mnemonic (fex, sfrA, and cpxC, respectively).…”
mentioning
confidence: 99%
“…aroH codes for one of the three 3-deoxy-2-keto-D-arabinoheptulosonic acid 7-phosphate (DAHP) synthases that catalyze the first step in aromatic amino acid biosynthesis (9,10). trpR was recently cloned from the E. coli chromosome onto phage and plasmid vectors (11,12). The gene is present on a 1.3-kilobase BamHI fragment (11,12).…”
mentioning
confidence: 99%